SYNDROME IN QUESTION - Nilton Di Chiacchio; Julio Cesar Jasso-Olivares; Nilton Gioia Di Chiacchio; José Antonio Jacinto; Maria Victoria Suárez Restrepo (Sociedade Brasileira de Dermatologia, 2015)
Abstract The Iso-Kikuchi Syndrome is a rare condition characterized by nail dysplasia involving the index fingers, including micronychia, polyonychia, anonychia, irregular lunula, malalignment and hemionychogryphosis. On the antero-posterior image, radiologic examination reveals a narrowing of the distal phalanx. The lateral image shows a Y-shaped bifurcation of the distal phalanx. We report a case of a patient with typical clinical and radiologic signs of Iso-Kikuchi Syndrome.